Karakteristik Morfologi Tanaman Mentha spicata Hasil Induksi Ekstrak Etanolik Daun Tapak Dara (Catharanthus Roseus) - Rivo Yulse Viza (Pendidikan Biologi STKIP YPM Bangko, 2019)
Mentha spicata is an herbal plant producing spearmint oil commonly used in the herbal medicine industry, soap, toothpaste and cosmetics. The main place for producing spearmint oil is leaves. To improve the quality of leaves can be achieved by increasing the size of leaf cells through the polyploidization technique with natural mutagen that is ethanolic extract of Tapak dara leaf. This research is an experimental research with Completely Randomized Design with ethanolic extract concentration of 0,1% with application frequency which were 2 drop per day for a day, 2 drop per day for 2 days, and 2 drop per day for 3 days. The observed parameters were number of shoot, number of leaf, stem diameter, leaf area and stem height. Based on the observations, application of ethanolic extract concentration of 0,1% with application frequency 2 drop for a day and 2 drop for 2 days against real controls on the number of root and leaf area parameter. In addition, T-test showed significantly differnt result from the control on stem diameters with ethanolic extract concentration of 0,1%, application frequency 2 drop for 2 days.